ANALISIS PEDOMAN PENILAIAN RISIKO DAN PENERAPANNYA PADA PENYUSUNAN APBD PROVINSI DKI JAKARTA - Fika Ayu Wanditha; M. Yusuf John (Program Studi S1 Akuntansi Fakultas Ekonomi & Bisnis Univesitas Jenderal Soedirman, 2018)
This study aims to analyze the guidelines for the implementation of risk assessment prepared by the Financial and Development Supervisory Agency (BPKP) by using risk management theory and to conduct a trial of the application of the analysis results in risk assessment activities in the process of preparing Regional Revenue and Expenditure Budget (APBD) DKI Jakarta Province. This research is based on the results of coaching activities carried out by the Representative Office of the DKI Jakarta Province, namely by assessing the maturity level of SPIP implementation in the Provincial Government of DKI Jakarta in 2015, assessing two focus elements of risk assessment, namely risk identification and risk analysis that still get Zero value, namely in each work unit within the DKI Jakarta Provincial Government does not have a formal risk assessment guideline so that each work unit does not have a risk register and the results of risk analysis that can be used to make control action plans or risk management plans for key activities formally determined. The theory used in this research is risk management theory as stated by Spikin (2013). This study uses the Mixed-Method method, which combines quantitative and qualitative research methods by means of observation, in-depth interviews, reviewing data from other documents or literature and questionnaires. The results of this study indicate that the risk assessment guidelines that have been prepared by BPKP need to be refined in accordance with the elements of risk management so that the risk assessment guidelines can be applied in the risk assessment activities in the process of preparing the DKI Jakarta Provincial Budget.